Metabolic evaluation of recurrent idiopathic calcium stone disease in Portugal. - Serra, Adelaide (2004)
Idiopathic calcium stone disease is the most frequent type of nephrolithiasis in industrialised countries. Several metabolic, environmental and genetic factors have described and may be involved in its pathogenesis. This study was designed to evaluate the factors that contribute to idiopathic calcium stone disease in Portugal.To characterise the Portuguese population with idiopathic recurrent calcium stone disease, a population of 87 consecutive idiopathic recurrent calcium stone formers (IRCSF) was evaluated over a 5-year period. The results were compared with a control group of 45 healthy subjects (HS) from the same population, with similar age and gender distribution.No difference was observed in the distribution of affected individual according to gender (47 females and 40 males). A familial history of nephrolithiasis was present in 35.6%. Significantly higher urinary calcium and lower urinary citrate were observed in IRCSF group when compared with HS group. Individual analysis revealed urinary abnormalities in 78 of 87 IRCSF (89.7%). Hyperoxaluria was the most frequent abnormality, observed in 40.2% of the patients, hyperuricosuria in 33.3%, hypercalciuria in 24.1%, hypocitraturia in 23.0%, low urine volume in 19.5% and hypomagnesiuria in 8%. No difference was observed in the distribution of urinary risk factors according to gender or presence of familial antecedents of nephrolithiasis. A positive correlation was observed between urinary sodium and calcium in hypercalciuric patients.Among the studied population, idiopathic calcium nephrolithiasis affected both genders equally. Metabolic evaluation permits the identification of urine abnormalities in most of these patients. Hyperoxaluria, hypercalciuria, hypocitraturia and hyperuricosuria appeared as important pathogenic factors in IRCSF. Urine volume was not different between groups. Dietary factors may be involved in the observed urine abnormalities and need to be further evaluated.